Transmedia narrative and representation of the gamer to generate emotional connection: Pepsi Case - Pardo-Price, Aaron (2024)
The study analyzes the perception of young gamers (18-28 years old) in the district of San Miguel (Lima, Peru) about the emotional connection in the representation of video gamers, focusing on Pepsi’s “1 Slurp = 1 Blue” campaign. Using a qualitative case study approach, three categories are explored: transmedia narrative, gamers’ representation and emotional connection. This allows for a more direct and personalized experience, challenging negative stereotypes about gamers. The key role of music and sound in video games in intensifying the emotional user experience is highlighted. The findings suggest that the campaign succeeds in authentically representing video gamers, building a strong emotional connection through interactive challenges, inclusion of local influencers and diverse representation. It effectively captured the preferences and needs of the target audience, maintaining authenticity and building a genuine emotional connection with the audience.